1990
DOI: 10.1148/radiology.174.1.2152983
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal neoplasms after intraarterial chemotherapy: correlation of MR images with pathologic specimens.

Abstract: The most accurate prognostic indicator in patients with musculoskeletal sarcomas is the percentage of tumor necrosis after intraarterial chemotherapy. Magnetic resonance (MR) imaging was evaluated to determine its ability to indicate the percentage of necrosis in musculoskeletal neoplasms after treatment. Fourteen patients with musculoskeletal neoplasms underwent treatment protocols including intraarterial chemotherapy (n = 14), radiation therapy (n = 6), and systemic chemotherapy (n = 14). All patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…T2 signal intensities were increased in 89.9% (types 2 and 3) of all lesions and mainly considered the result of tumor necrosis. But Sanchez et al 23 correlated pathologic specimens of primary musculoskeletal neoplasms after chemotherapy with MR images, and reported that areas of high signal intensity on T2WI corresponded to areas of residual viable tumor, tumor necrosis, edema, fibrosis, and hemorrhage. In our study, decreased but persistent contrast enhancement was observed in the area of increased T2 signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…T2 signal intensities were increased in 89.9% (types 2 and 3) of all lesions and mainly considered the result of tumor necrosis. But Sanchez et al 23 correlated pathologic specimens of primary musculoskeletal neoplasms after chemotherapy with MR images, and reported that areas of high signal intensity on T2WI corresponded to areas of residual viable tumor, tumor necrosis, edema, fibrosis, and hemorrhage. In our study, decreased but persistent contrast enhancement was observed in the area of increased T2 signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only limited differentiation between group 2 (necrosis over 80%) and group 3 (viable tumor cells up to 95%) was possible ; this was because technical factors including window selection and volume averaging were involved. Thus tumor necrosis cannot be predicted on the basis of signal intensity alone, and because the appearances of viable tumor, necrosis, edema, fibrosis, granulation tissue, and hemorrhage overlap, changes in signal intensity do not reliably indicate the absence of active disease (5). Moreover, small clusters of active tumor cells were found in areas of dense reactive bones (7).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemotherapy is used to reduce tumoral volume [9,10], allow limb salvage surgery, eradicate micrometastases, and test therapeutic efficacy [1,3,9]. The percentage of tumor necrosis induced by preoperative chemotherapy is one of the essential prognostic factors [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…It induces effects on the tumor and also on surrounding normal tissues. These local undesirable effects on the normal tissues may be misdiagnosed as a tumoral progression under chemotherapy [7][8][9]. We report abnormal images with MRI examination appearing on the distal femur after intraarterial chemotherapy (IAC) for osteosarcoma of the tibia in one case, the fibula in the other.…”
mentioning
confidence: 98%